ANALYSIS OF PROFESSIONAL ARTICLES ON LEGAL ISSUES IN PUBLICISTIC STYLE - Apresyan, Margaret; Karapetyan, Mariam (Foreign Languages for Special Purposes, 2025)
The present paper studies professional articles on legal issues targeted at a broad readership focusing on their stylistic and genre-based diversity. The study shows that the articles noted above blend features of both scientific and publicistic styles utilizing expressive stylistic devices determined by their communicative tasks and goals to target a wider range of audience.